Understanding the mechanism of action of the glycosylated bacteriocin glycocin F : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biochemistry at Massey University, Manawatu, New Zealand - Bisset, Sean William (Massey University, 2019)
With the increasing threat posed by antibiotic-resistant bacteria, eﬀorts must be made to ﬁnd new antimicrobial agents. One growing area of promise is the bacteriocins, which are a diverse group of antimicrobial peptides produced by bacteria. This thesis focuses on determining the mechanism of action of one of these peptides, glycocin F (GccF). GccF is produced by the bacterium Lactobacillus plantarum and is modiﬁed with two N-acetyl glucosamine (GlcNAc) sugar moieties, one located on an interhelical loop region, and the other at the end of a ﬂexible C-terminal ‘tail’. It has also been shown to exhibit a unique eﬀect on susceptible bacteria, putting them into a reversible state of hybernation as opposed to outright killing them. However, little is known about the roles of the structural features of GccF, how it triggers bacteriostasis in target cells, or even what part(s) of bacterial cells it targets. This work addresses these questions using three main approaches: studying the structure-function relationship of diﬀerent parts of GccF with chemically synthesised analogues; looking at the transcriptional response of a pathogenic bacteria, Enterococcus faecalis, to GccF; and trying to identify binding partners of GccF and its respective immunity protein, GccH. The results presented here highlight diﬀerent roles of the GlcNAcs attached to GccF, with both the interhelical loop and presence of GlcNAc on this loop being vital for activity, while the sugar at the C-terminal position is important, but not crucial for the peptide’s activity. Additionally, a role of the GlcNAc phosphotransferase system on the mechanism of GccF is strongly indicated, with evidence from both the transcriptional studies and the protein interaction studies of GccF’s immunity protein. Taken together, the results allow for two theoretical models of GccF’s mechanism of action to be proposed. These models presented here should serve to increase the understanding of other glycocin-class bacteriocins and their mechanisms of action, and possibly contribute towards the creation of a blueprint for a new class of antimicrobial agents.
Figures are re-used with their respective publisher's permission or under a Creative Commons Attribution 4.0 International (CC BY 4.0) license.
Keywords: Bacteriocins; Peptide antibiotics; Lactobacillus plantarum; Lactobacillus; Genetics; 310112 Structural biology (incl. macromolecular modelling)